Relationship Between Breastfeeding Self-efficacy, Breastfeeding Motivation, and Self-esteem - Başak Ünsal Çimen; Cansu Akdağ Topal; Handan Boztepe (Galenos Publishing House, 2024)
Objective: This study examined the relationship between breastfeeding self-efficacy, breastfeeding motivation, and self-esteem. Method: This cross-sectional study was conducted with 260 postpartum women at Gazi University Hospital between November 20, 2022, and March 1, 2023. The data collection tools included a socio-demographic form, the breastfeeding self-efficacy scale, the breastfeeding motivation scale, and the Rosenberg self-esteem scale. Results: In the study, the mothers' breastfeeding self-efficacy scale mean score was 56.11±5.34, the Rosenberg self-esteem scale mean score was 14.51±0.78, and the breastfeeding motivation scale mean score was 69.98±5.15. According to the structural model, the results demonstrated that there was a positive significant relationship between breastfeeding self-efficacy and breastfeeding motivation (p<0.05) and between breastfeeding self-efficacy and self-esteem (p<0.05). Conclusion: The findings indicated that socio-demographic factors did not significantly influence breastfeeding self-efficacy, while social support and number of births were significant factors. It was determined that a significant relationship existed between breastfeeding self-efficacy and self-esteem.